2021
DOI: 10.3390/genes12070965
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomes Reveal Two Major Influxes of Papuan Ancestry across Wallacea Following the Last Glacial Maximum and Austronesian Contact

Abstract: The tropical archipelago of Wallacea contains thousands of individual islands interspersed between mainland Asia and Near Oceania, and marks the location of a series of ancient oceanic voyages leading to the peopling of Sahul—i.e., the former continent that joined Australia and New Guinea at a time of lowered sea level—by 50,000 years ago. Despite the apparent deep antiquity of human presence in Wallacea, prior population history research in this region has been hampered by patchy archaeological and genetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
3
24
0
Order By: Relevance
“…The prevailing view of regional history is of two major human movements—the initial settlement ( Leavesley and Chappell 2004 ; Summerhayes et al 2010 ; Clarkson et al 2017 ; O’Connell et al 2018 ) and the arrival of Austronesian speakers 3–3.5 kya ( Bellwood 2004 , 2006 ), implicitly suggesting that little occurred in this region during the Upper Pleistocene. However, the more resolved chrY tree with denser sampling uncovers a far more complex paternal demographic history, consistent with some of the newer studies in genetics ( Gomes et al 2015 ; Pedro et al 2020 ; Purnomo et al 2021 ), linguistics ( Schapper 2017 ), and archaeology ( Summerhayes 2007 ; Summerhayes et al 2017 ; Bellwood 2019 ). In particular, the increase in genetic lineage diversification correlates well with increasing population interactions and population sizes postulated from the archaeological record around 25–20 kya, based on animal, plant, and object (e.g., obsidian) translocation between Northern Sahul regions, changes in the subsistence economy, increasing occupation of Highland New Guinea, and settlement of distant islands (e.g., Manus), all of which suggest population size increases and connection of local dynamics to larger regional networks ( Leavesley and Chappell 2004 ; Specht 2005 ; Summerhayes 2007 ; Summerhayes et al 2017 ).…”
Section: Resultssupporting
confidence: 69%
“…The prevailing view of regional history is of two major human movements—the initial settlement ( Leavesley and Chappell 2004 ; Summerhayes et al 2010 ; Clarkson et al 2017 ; O’Connell et al 2018 ) and the arrival of Austronesian speakers 3–3.5 kya ( Bellwood 2004 , 2006 ), implicitly suggesting that little occurred in this region during the Upper Pleistocene. However, the more resolved chrY tree with denser sampling uncovers a far more complex paternal demographic history, consistent with some of the newer studies in genetics ( Gomes et al 2015 ; Pedro et al 2020 ; Purnomo et al 2021 ), linguistics ( Schapper 2017 ), and archaeology ( Summerhayes 2007 ; Summerhayes et al 2017 ; Bellwood 2019 ). In particular, the increase in genetic lineage diversification correlates well with increasing population interactions and population sizes postulated from the archaeological record around 25–20 kya, based on animal, plant, and object (e.g., obsidian) translocation between Northern Sahul regions, changes in the subsistence economy, increasing occupation of Highland New Guinea, and settlement of distant islands (e.g., Manus), all of which suggest population size increases and connection of local dynamics to larger regional networks ( Leavesley and Chappell 2004 ; Specht 2005 ; Summerhayes 2007 ; Summerhayes et al 2017 ).…”
Section: Resultssupporting
confidence: 69%
“…the Liang Toge individual, being considerably shorter (c.15cm) than the female from Liang Lembudu [45,59]. These calculations confirm the small size of this individual as defined by the craniometrics.…”
Section: Plos Onesupporting
confidence: 66%
“…The recovery of the postcranial skeleton from TLB-1 permits us to confirm the female sex of this individual, which is relevant to discussions about gender roles in prehistory [ 8 ]. Additionally, the stature estimation places this individual within the range of Javanese females and the Liang Toge individual, being considerably shorter (c.15cm) than the female from Liang Lembudu [ 45 , 59 ]. These calculations confirm the small size of this individual as defined by the craniometrics.…”
Section: Discussionmentioning
confidence: 99%
“…Future ancient DNA data will be important to calibrate absolute genetic dating approaches ( Wohns et al., 2022 ), but it still represents a major technical challenge in tropical areas such as in most of Oceania ( Carlhoff et al., 2021 ; Oliveira et al., 2021 ). Our relative dating approach is limited by demographic movements between Wallacea and New Guinea, following the initial settlement of Sahul, which we previously described ( Brucato et al., 2021 ; Purnomo et al., 2021 ). Population migrations out of New Guinea led to extensive gene flows, especially in Wallacea ( Oliveira et al., 2021 ), which could influence our results, because we assigned our Wallacean data as the ancestral group.…”
Section: Discussionmentioning
confidence: 99%
“…Since human genetic diversity west of the Wallace line is largely dominated by Asian ancestry ( Hudjashov et al., 2017 ; Lipson et al., 2014 ), the Wallacean population on Flores Island is the best proxy in our dataset of modern genomes for a genetic signature prior to the initial settlement of north Sahul. Previous reports showed that secondary gene flows from New Guinea to Wallacea occurred during the last 20,000 years ( Brucato et al., 2021 ; Carlhoff et al., 2021 ; Oliveira et al., 2021 ; Purnomo et al., 2021 ) but they do not affect the ability to detect signals related to earlier phases of human history ( Brucato et al., 2021 ; Jacobs et al., 2019 ). Results of these selection scans were normalized with the norm function of Selscan v.1.3.0 ( Szpiech and Hernandez, 2014 ).…”
Section: Methodsmentioning
confidence: 98%